2009
DOI: 10.1002/chem.200802373
|View full text |Cite
|
Sign up to set email alerts
|

Linker Conjugation Effects in Rhenium(I) Bifunctional Hole‐Transport/Emitter Molecules

Abstract: Spectroscopic, electrochemical and density functional theory (DFT) methods have been employed to investigate a group of [Re(CO)(3)(HT)(phen)](+) complexes (phen = 1,10-phenanthroline), and in particular the level of electronic communication between various hole-transporting (HT) ligands and the rhenium centre. Here, the HT ligand consists of a coordinating pyridine connected to dimethylaniline group through a single-, double- or triple-bond-connecting system. Electronic absorption, resonance Raman, and steady-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 52 publications
(56 reference statements)
0
29
0
Order By: Relevance
“…The cobalt-oxo cubane [Co 4 O 4 (CO 2 Py) 2 (bpy) 4 ](ClO 4 ) 2 (1, CO 2 Py = 4-carboxypyridine) was obtained from isonicotinic acid and [Co 4 O 4 (CO 2 Me) 2 (bpy) 4 ](ClO 4 ) 2 by using methods adapted from those reported by Christou [33] (see the Experimental Section and the Supporting Information for synthetic details and full characterisation). Complexation of this functionalised cubane with the rhenium-based photosensitiser [Re(phen)(CO) 3 -(CH 3 CN)]PF 6 [34] (phen = 1,10-phenanthroline) affords a cobaltoxo cubane core ligated by Re I phenanthroline photocentres (2).…”
Section: Resultsmentioning
confidence: 99%
“…The cobalt-oxo cubane [Co 4 O 4 (CO 2 Py) 2 (bpy) 4 ](ClO 4 ) 2 (1, CO 2 Py = 4-carboxypyridine) was obtained from isonicotinic acid and [Co 4 O 4 (CO 2 Me) 2 (bpy) 4 ](ClO 4 ) 2 by using methods adapted from those reported by Christou [33] (see the Experimental Section and the Supporting Information for synthetic details and full characterisation). Complexation of this functionalised cubane with the rhenium-based photosensitiser [Re(phen)(CO) 3 -(CH 3 CN)]PF 6 [34] (phen = 1,10-phenanthroline) affords a cobaltoxo cubane core ligated by Re I phenanthroline photocentres (2).…”
Section: Resultsmentioning
confidence: 99%
“…It will be demonstrated that the SO model accounts very well for absorption spectra, emission properties, and excited-state dynamics, some of its conclusions being qualitatively different from the spinfree approach. [Re(imH)(CO) 3 (phen)] + represents a broad class of Re I tricarbonyl-diimine complexes [21][22][23], which show very rich photophysics and photochemistry [10,14,15,24] and engage in a range of photonic applications such as photosensitizers and phototriggers of electron-transfer reactions [11,[25][26][27][28][29], photocatalysts of CO 2 reduction [30][31][32], phosphorescent labels and probes of biomolecules [33][34][35][36], sensors [37,38], molecular switches [39][40][41][42] and OLED emitters [43], or probes of ps-ns dynamics of solvents, proteins or supramolecular hosts [11,24,50,51,[63][64][65]. The chosen example [Re(imH)(CO) 3 (phen)] + [44] not only epitomizes the salient features of Re I carbonyl-diimine photophysics but also has a prominent position amongst Re-based photosensitizers because of its ability to trigger photoinduced electron transfer and relaxation dynamics in Re-labeled proteins [11,25,[44]…”
Section: Introductionmentioning
confidence: 99%
“…The resulting mean absolute deviations (MADs) of the frequencies are shown in Table 4; the values are indicative of satisfactory calculations. [29,[43][44][45][47][48][49][50][51] …”
Section: Synthesis and Characterisation Of Polyphosphazenesmentioning
confidence: 99%
“…Normal modes that mimic ground-to excited-state geometry changes are preferentially enhanced in intensity and this enables unambiguous assignments to be made of chromophorically active regions in a molecule. [44,47,56,57] respectively, and have therefore been omitted for clarity. The spectrum of [(L 1 -H)PtCl] acquired at 350.7 nm shows resonance-enhancement at 1358, 1483 and around 1610 cm -1 , which are identified as modes delocalised over the entire OPhbpyPh unit with significant contributions from both Ph units.…”
Section: Resonance Raman Spectramentioning
confidence: 99%